2012
DOI: 10.5194/amt-5-1459-2012
|View full text |Cite
|
Sign up to set email alerts
|

Development of a parallel sampling and analysis method for the elucidation of gas/particle partitioning of oxygenated semi-volatile organics: a limonene ozonolysis study

Abstract: The gas/particle partitioning behaviour of the semi-volatile fraction of secondary organic matter and the associated multiphase chemistry are key features to accurately evaluate climate and health impacts of secondary organic aerosol (SOA). However, today, the partitioning of oxygenated secondary species is rarely assessed in experimental SOA studies and SOA modelling is still largely based on estimated partitioning data. This paper describes a new analytical approach, solvent-free and easy to use, to explore … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 125 publications
1
26
0
Order By: Relevance
“…This is especially critical when investigating unknown and/or multi-functionalized compounds. In these cases, alternative approaches can be necessary such as the use of different derivatization procedures 222,242 on different samples in the same series, or the derivatization of different fractions of a sample that was first fractionated by flash chromatography 243 prior to GC/MS analysis. 244 More common approaches include multi-step derivatizations, which target the different hydroxyl, carboxylic acid, and/or keto-or aldehyde groups of multifunctional compounds.…”
Section: Derivatizationmentioning
confidence: 99%
“…This is especially critical when investigating unknown and/or multi-functionalized compounds. In these cases, alternative approaches can be necessary such as the use of different derivatization procedures 222,242 on different samples in the same series, or the derivatization of different fractions of a sample that was first fractionated by flash chromatography 243 prior to GC/MS analysis. 244 More common approaches include multi-step derivatizations, which target the different hydroxyl, carboxylic acid, and/or keto-or aldehyde groups of multifunctional compounds.…”
Section: Derivatizationmentioning
confidence: 99%
“…Figure 2 shows an example of a mass spectrum from one of the experiments. Over 100 different molecular formulas for acids have been identified, far exceeding the number of acids reported in previous studies (Glasius et al, 2000;Leungsakul et al, 2005a;Jaoui et al, 2005Jaoui et al, , 2006Walser et al, 2008;Rossignol et al, 2012Rossignol et al, , 2013. Here we will focus on the analysis of acids with carbon numbers ranging from seven to ten (and the dimers formed from these acids).…”
Section: Resultsmentioning
confidence: 98%
“…Explicit formation pathways for the compounds C 10 H 16 O 4 and C 9 H 12 O 5 implemented in the MCM and additional reaction pathways for C 7 H 10 O 4 , C 8 H 12 O 4−5 , C 9 H 14 O 4−5 and C 10 H 16 O 3 are proposed. Structures for C 10 H 14 O 5 and C 10 H 16 O 4 have been proposed in previous studies (Glasius et al, 2000;Leungsakul et al, 2005a;Jaoui et al, 2006;Walser et al, 2008;Rossignol et al, 2012) but the current mechanistic understanding is inadequate for explaining the formation of compounds with the proposed structures. In fig.…”
Section: Mechanism Interpretation and Outlookmentioning
confidence: 99%
“…The study of oxygenated volatile organic compounds (OVOCs) in the atmosphere of biogenic origin, and the degradation products resulting from their tropospheric oxidant mediated photooxidation, is of importance due to the high reactivity and ozone formation potential of many of these compounds which makes them substantial contributors to the formation of photochemical smog and secondary organic aerosol (SOA) 1 There have been a number of studies and evaluation of data on the reactions of ozone with unsaturated alcohols reported in the literature [4][5][6][7][8][9][10][11] . However, reactivity and mechanistic information for the reaction of ozone with the hexenols isomers is limited.…”
Section: Introductionmentioning
confidence: 99%